Adhesive composition, and adhesive formed by crosslinking the same, as well as adhesive tape
A pressure-sensitive adhesive composition with specific acrylic resin and metal chelate crosslinking agent addresses the balance of adhesive properties and environmental concerns, ensuring strong, tacky, and residue-free removal on soft plastics.
Patent Information
- Application Number
- JP2024050704
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2024-03-27
- Publication Date
- 2025-10-09
AI Technical Summary
Existing adhesive technologies fail to achieve a balance of adhesive properties such as strength, tack, and peelability, particularly on soft plastic surfaces, while also not being environmentally friendly due to petroleum-based materials and leaving residue upon removal.
A pressure-sensitive adhesive composition using an acrylic resin with specific structural units and a metal chelate crosslinking agent, derived from renewable resources, achieving a balance of adhesive properties and peelability.
The composition provides a pressure-sensitive adhesive with excellent adhesive strength, tack, and peelability without residue on soft plastics, certified as environmentally friendly.
Smart Images

Figure 2025150044000001 
Figure 2025150044000002 
Figure 2025150044000003
Abstract
Description
[Technical Field]
[0001] The present invention relates to a pressure-sensitive adhesive composition containing an acrylic resin and a tackifier resin that are suitable as a pressure-sensitive adhesive, and more specifically to a pressure-sensitive adhesive composition and pressure-sensitive adhesive that have a good balance of adhesive properties (adhesive strength, holding power, tack) and peelability, and that can be made from biologically derived raw materials. [Background technology]
[0002] In recent years, adhesive tapes have been used in a variety of industrial fields, including home appliances, automobiles, office automation equipment, and construction, as a joining method that offers good workability and highly reliable adhesion. For example, during the construction of a building, when interior work is carried out after flooring materials have been laid, the flooring materials are covered with a floor protection sheet to prevent damage to the flooring materials, and adhesive tape is used to secure the floor protection sheet in place. The adhesive tape used for such purposes is peeled off and removed together with the floor protection sheet after the purpose of protecting the flooring materials has been completed.
[0003] Furthermore, acrylic adhesives often use petroleum as a raw material, and carbon dioxide is emitted during disposal after use. This raises concerns about the depletion of petroleum resources and their impact on global warming, and the use of plant-derived raw materials, which are renewable, is therefore recommended.
[0004] As examples of adhesives and adhesive tapes used for such protective purposes, Patent Document 1, for example, describes a protective tape that is an adhesive composition having excellent adhesive properties (adhesive strength, tack) and peelability, and that leaves no adhesive residue when peeled off, even from flooring materials made of particularly soft plastics. Patent documents 2 and 3 describe adhesive compositions that are partially derived from renewable resources, plant-based materials. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Japanese Patent Application Laid-Open No. 2015-189842 [Patent Document 2] Special Publication No. 2010-506979 [Patent Document 3] Special Publication No. 2011-516690 Summary of the Invention [Problem to be solved by the invention]
[0006] However, the technology disclosed in the above-mentioned document 1 utilizes terpene-based biological resources (biomass) that are said to be derived from plants, but there is a problem in that it is not at a level that would prevent it from being certified as an environmentally friendly product. The technologies disclosed in documents 2 and 3 do not fully satisfy the adhesive properties of adhesive strength and tack, and there is a problem in that these issues cannot be met simultaneously.
[0007] Under these circumstances, the present invention aims to provide an adhesive composition for obtaining an adhesive that has a good balance of adhesive properties (adhesive strength, tack, holding power) and releasability for a variety of adherends, and in particular an acrylic adhesive composition that can be used as a protective tape without leaving adhesive residue even on soft plastic flooring materials. [Means for solving the problem]
[0008] However, in light of these circumstances, the present inventors have conducted extensive research and have found that, in a pressure-sensitive adhesive composition containing an acrylic resin (A) and a crosslinking agent (B), by using an acrylic resin containing specific structural units in specific amounts and a metal chelate crosslinking agent, it is possible to provide a pressure-sensitive adhesive that has a good balance of adhesive properties (adhesive strength, tack, holding power) and releasability for a variety of adherends, and have completed the present invention.
[0009] That is, the gist of the present invention relates to the following [1] to [6]. [1] A pressure-sensitive adhesive composition containing an acrylic resin (A) and a crosslinking agent (B), With respect to all structural units of the acrylic resin (A), the content of structural units derived from 1-methylheptyl (meth)acrylate (a1) is 10 to 90% by weight, and the content of structural units derived from ethylenically unsaturated monomers containing a functional group (a2) is 0.1 to 10% by weight, The pressure-sensitive adhesive composition, wherein the crosslinking agent (B) contains a metal chelate crosslinking agent (b1). [2] The pressure-sensitive adhesive composition according to [1], wherein the acrylic resin (A) has a glass transition temperature (Tg) of −30° C. or lower. [3] The pressure-sensitive adhesive composition according to [1] or [2], wherein the content of the crosslinking agent (B) is 0.01 to 5 parts by weight based on 100 parts by weight of the acrylic resin (A). [4] The pressure-sensitive adhesive composition according to any one of [1] to [3], wherein the proportion of plant-derived carbon in the entire pressure-sensitive adhesive composition is 10% by weight or more. [5] [1] [4] A pressure-sensitive adhesive obtained by crosslinking the pressure-sensitive adhesive composition according to any one of [1] to [4]. [6] An adhesive tape characterized by having an adhesive layer made of the adhesive according to claim [5].
[0010] Furthermore, the present invention relates to a pressure-sensitive adhesive obtained by using the pressure-sensitive adhesive composition, and a pressure-sensitive adhesive tape using the same. It is related to.
[0011] In addition, in the present invention, raw materials partially derived from renewable resources and plant materials are used, and by adjusting the ratio of the constituent raw materials and the type and amount of crosslinking agent, a product with an excellent balance of adhesive properties and peelability is obtained that has been certified as an environmentally friendly product. [Effects of the Invention]
[0012] The pressure-sensitive adhesive composition of the present invention is a pressure-sensitive adhesive composition for obtaining a pressure-sensitive adhesive that has a good balance of adhesive properties (adhesive strength, tack, holding power) and releasability for a variety of adherends, and is particularly useful as a protective tape that does not leave adhesive residue when removed from flooring materials made of soft plastics. DETAILED DESCRIPTION OF THE INVENTION
[0013] The present invention will be described in detail below. In the present invention, (meth)acrylic acid means acrylic acid or methacrylic acid, (meth)acrylic means acrylic or methacrylic, (meth)acryloyl means acryloyl or methacryloyl, and (meth)acrylate means acrylate or methacrylate, respectively. In the present invention, when the expression "X to Y" (X and Y are any numbers) is used, unless otherwise specified, it means "X or more and Y or less," as well as "preferably larger than X" or "preferably smaller than Y." Furthermore, when it is expressed as "X or more" (X is any number) or "Y or less" (Y is any number), it also means that "it is preferably greater than X" or "it is preferably less than Y." In the present specification, in which multiple numerical ranges are described in stages, each upper limit and each lower limit may be the upper limit or lower limit of any combined numerical range. For example, when the content of a certain component is described as "5 to 20% by weight, 10 to 15% by weight," each of the numerical ranges may be "5 to 15% by weight," "10 to 20% by weight," "5 to 10% by weight," or "15 to 20% by weight."
[0014] First, the acrylic resin (A) contained as an essential component in the pressure-sensitive adhesive composition of the present invention will be described. The acrylic resin (A) contains a structural unit derived from 1-methylheptyl (meth)acrylate (a1), a structural unit derived from an ethylenically unsaturated monomer (a2) containing a functional group, and a structural unit derived from a vinyl ester (a3), and optionally contains a structural unit derived from another monomer (a4). The content of each monomer relative to the total copolymerization component (a) can be considered to be the content of structural units derived from that monomer in the acrylic resin (A) which is a copolymer. For example, the content of the carboxyl group-containing monomer (a2-1) relative to the total copolymerization component (a) can be considered to be the content of structural units derived from the carboxyl group-containing monomer (a2-1) in the acrylic resin (A).
[0015] The content of the structural units derived from 1-methylheptyl (meth)acrylate (a1) is 10 to 90% by weight, preferably 15 to 90% by weight, more preferably 25 to 90% by weight, and even more preferably 35 to 90% by weight, based on the total structural units of the acrylic resin (A). When the content of the structural unit derived from 1-methylheptyl (meth)acrylate (a1) is within the above range, the adhesive strength and tackiness are good. On the other hand, if there is too much, the tackiness will be lost, and if there is too little, the amount of plant-derived raw materials used, which are renewable materials, will be reduced and the product will not be recognized as environmentally friendly.
[0016] Examples of the ethylenically unsaturated monomer (a2) containing the functional group include carboxyl group-containing unsaturated monomers (a2-1) such as (meth)acrylic acid, crotonic acid, maleic acid, maleic anhydride, itaconic acid, fumaric acid, (meth)acrylamide-N-glycolic acid, cinnamic acid, Michael adducts of (meth)acrylic acid (e.g., (meth)acrylic acid dimer, (meth)acrylic acid trimer, (meth)acrylic acid tetramer, 2-(meth)acryloyloxyethyl dicarboxylic acid monoesters (e.g., 2-(meth)acryloyloxyethyl succinic acid monoester, 2-(meth)acryloyloxyethyl phthalic acid monoester, 2-(meth)acryloyloxyethyl hexahydrophthalic acid monoester, etc.); Hydroxyl group-containing unsaturated monomers such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-chloro 2-hydroxypropyl (meth)acrylate, tetrahydrofurfuryl (meth)acrylate, 2-hydroxy 3-phenoxypropyl (meth)acrylate, diethylene glycol (meth)acrylate, polyethylene glycol (meth)acrylate, and N-methylol (meth)acrylamide; glycidyl group-containing unsaturated monomers such as glycidyl (meth)acrylate and allyl glycidyl (meth)acrylate; Isocyanate group-containing unsaturated monomers such as 2-(meth)acryloyloxyethyl isocyanate; amide group-containing unsaturated monomers such as (meth)acrylamide, N-(n-butoxyalkyl)(meth)acrylamide, (meth)acrylamide-3-methylbutylmethylamine, dimethylaminoalkyl(meth)acrylamide, dimethyl(meth)acrylamide, and diethyl(meth)acrylamide; Sulfonic acid group-containing unsaturated monomers such as olefin sulfonic acids such as ethylene sulfonic acid, allyl sulfonic acid, and methallylsulfonic acid, 2-(meth)acrylamido-2-methylpropanesulfonic acid, styrene sulfonic acid, and salts thereof; Amino group-containing unsaturated monomers such as dimethylaminoethyl (meth)acrylate and diethylaminoethyl (meth)acrylate; At least one selected from these is used. Among these, carboxyl group-containing unsaturated monomers, hydroxyl group-containing unsaturated monomers, glycidyl group-containing unsaturated monomers, isocyanate group-containing unsaturated monomers, and amide group-containing unsaturated monomers are preferably used, and carboxyl group-containing unsaturated monomers and hydroxyl group-containing unsaturated monomers are particularly preferred.
[0017] The content of the ethylenically unsaturated monomer (a2) containing the above functional group is preferably 0.1 to 10% by weight, particularly preferably 0.3 to 9% by weight, further preferably 0.5 to 7% by weight, and particularly preferably 1 to 5% by weight, based on all structural units. When the content of the structural unit derived from the ethylenically unsaturated monomer (a2) containing the functional group is within the above range, a good balance between holding power and adhesive power is achieved. On the other hand, if the amount is too large, the pot life during coating will be shortened, and if the amount is too small, crosslinking will not proceed and cohesion will be poor.
[0018] Examples of the vinyl ester (a3) (excluding 1-methylheptyl (meth)acrylate (a1) and the monomer (a2)) include vinyl acetate, vinyl propionate, vinyl versatate, and vinyl stearate. Among these, vinyl acetate is preferred because it is highly versatile and can easily impart cohesive strength.
[0019] The content of the structural units derived from the vinyl ester (a3) is preferably 0.1 to 30% by weight, particularly preferably 0.3 to 20% by weight, further preferably 0.5 to 15% by weight, and particularly preferably 1 to 10% by weight, based on the total structural units. When the content of the structural unit derived from the vinyl ester (a3) containing the functional group is within the above range, a good balance between ball tackiness and adhesive strength is achieved. If the amount is too large, polymerization becomes difficult and residual monomers remain, which can easily cause odor problems when the adhesive tape is used, whereas if the amount is too small, the cohesive strength becomes insufficient.
[0020] Examples of the other copolymerizable ethylenically unsaturated monomers (a4) (excluding 1-methylheptyl (meth)acrylate (a1), monomer (a2), and vinyl ester (a3)) include (meth)acrylic acid alkyl ester monomers having an alkyl group having 1 to 4 carbon atoms, such as methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, iso-butyl (meth)acrylate, and tert-butyl (meth)acrylate; (meth)acrylic acid alkyl ester monomers having an alkyl group having 5 or more carbon atoms, such as pentyl (meth)acrylate, isopentyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, isooctyl (meth)acrylate, isononyl (meth)acrylate, isodecyl (meth)acrylate, isodecyl (meth)methacrylate, isomistyryl (meth)acrylate, isostearyl (meth)acrylate, isoundecyl (meth)acrylate, isododecyl (meth)acrylate, isotridecyl (meth)acrylate, isopentadecyl (meth)acrylate, isohexadecyl (meth)acrylate, isoheptadecyl (meth)acrylate, 2-dodecyl-hexadecanyl (meth)acrylate, and 2-tetradecyl-octadecanyl (meth)acrylate; Aromatic ring-containing monomers such as phenyl (meth)acrylate, benzyl (meth)acrylate, phenoxyethyl (meth)acrylate, ethoxylated o-phenyl (meth)acrylate, phenoxydiethylene glycol (meth)acrylate, 2-hydroxy-3-phenoxypropyl (meth)acrylate, styrene, and α-methylstyrene; alicyclic structure-containing (meth)acrylic acid ester monomers such as cyclohexyl (meth)acrylate and isobornyl (meth)acrylate; 2-methoxyethyl (meth)acrylate, 2-ethoxyethyl (meth)acrylate, 3-methoxybutyl (meth)acrylate, and 2-butoxyethyl (meth)acrylate. Ether chain-containing (meth)acrylic acid ester monomers such as acrylate, 2-butoxydiethylene glycol (meth)acrylate, methoxydiethylene glycol (meth)acrylate, methoxytriethylene glycol (meth)acrylate, ethoxydiethylene glycol (meth)acrylate, methoxydipropylene glycol (meth)acrylate, methoxypolyethylene glycol (meth)acrylate, octoxypolyethylene glycol-polypropylene glycol-mono(meth)acrylate, lauroxypolyethylene glycol mono(meth)acrylate, and stearoxypolyethylene glycol mono(meth)acrylate; Acrylonitrile, methacrylonitrile, vinyl chloride, vinylidene chloride, alkyl vinyl ether, vinyl toluene, vinyl pyridine, vinyl pyrrolidone, itaconic acid dialkyl ester, fumaric acid Examples of compounds that can be used include dialkyl acrylate, allyl alcohol, acrylic chloride, methyl vinyl ketone, N-acrylamidomethyltrimethylammonium chloride, allyl trimethylammonium chloride, dimethyl allyl vinyl ketone, and (meth)acryloylmorpholine. These compounds can be used alone or in combination of two or more. Among these, vinyl acetate is preferred because it improves cohesive strength.
[0021] Furthermore, when the objective is to increase the molecular weight, polyfunctional monomers such as ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, propylene glycol di(meth)acrylate, and divinylbenzene can also be used in combination.
[0022] The content of the other copolymerizable ethylenically unsaturated monomer (a4) is preferably 0 to 20% by weight, particularly preferably 0.1 to 10% by weight, and even more preferably 0.2 to 5% by weight, based on the total weight of the polymerizable components. If the amount of the other copolymerizable ethylenically unsaturated monomer (a4) is too large, the copolymerizability of the polymer tends to decrease, and the other copolymerizable ethylenically unsaturated monomer (a4) tends to remain as a residual monomer and generate an odor.
[0023] The acrylic resin (A) used in the present invention can be produced by polymerizing 1-methylheptyl (meth)acrylate (a1) using an appropriately selected copolymerization component containing a functional group-containing ethylenically unsaturated monomer (a2), a vinyl ester (a3), or other copolymerizable ethylenically unsaturated monomer (a4). The polymerization can be carried out by a conventionally known method such as solution radical polymerization, suspension polymerization, bulk polymerization, or emulsion polymerization. For example, a polymerization component containing 1-methylheptyl (meth)acrylate (a1) and a polymerization initiator are mixed or dropped into an organic solvent, and polymerization is carried out under predetermined polymerization conditions. Among these polymerization methods, solution radical polymerization and bulk polymerization are preferred, and solution radical polymerization is more preferred.
[0024] Examples of the organic solvent used in the polymerization reaction include aromatic hydrocarbons such as toluene and xylene, aliphatic hydrocarbons such as hexane, esters such as ethyl acetate and butyl acetate, aliphatic alcohols such as n-propyl alcohol and isopropyl alcohol, and ketones such as acetone, methyl ethyl ketone, methyl isobutyl ketone, and cyclohexanone. Among these solvents, ethyl acetate, acetone, methyl ethyl ketone, butyl acetate, toluene, and methyl isobutyl ketone are preferred from the standpoint of ease of polymerization reaction, chain transfer effect, ease of drying when applying the adhesive, and safety, and ethyl acetate, acetone, and methyl ethyl ketone are more preferred.
[0025] Examples of polymerization initiators used in such radical polymerization include azo initiators such as 2,2'-azobisisobutyronitrile, 2,2'-azobis-2-methylbutyronitrile, 4,4'-azobis(4-cyanovaleric acid), and 2,2'-azobis(methylpropionic acid), which are common radical polymerization initiators, and organic peroxides such as benzoyl peroxide, lauryl peroxide, di-t-butyl peroxide, and cumene hydroperoxide, and can be appropriately selected and used depending on the monomer used. These solvents can be used alone or in combination of two or more.
[0026] The weight average molecular weight of the acrylic resin (A) is preferably from 300,000 to 1,800,000, particularly preferably from 400,000 to 1,500,000, and further preferably from 500,000 to 1,100,000. If the weight average molecular weight is too small, the cohesive strength will tend to decrease and the peelability will tend to decrease, whereas if the weight average molecular weight is too large, the adhesive strength will tend to decrease and production will tend to become difficult.
[0027] The dispersity (weight average molecular weight / number average molecular weight) of the acrylic resin (A) is preferably 3-8, particularly preferably 3.5-7.5, and further preferably 4-7. If the degree of dispersion is too high, the amount of low molecular weight components increases and the releasability tends to decrease, whereas if the degree of dispersion is too low, the adhesive strength tends to decrease and production tends to become difficult.
[0028] The weight-average molecular weights listed above are based on standard polystyrene molecular weights and are measured using a high-performance liquid chromatograph (Waters Japan, "Waters 2695 (main unit)" and "Waters 2414 (detector)") equipped with three Shodex GPC KF-806L columns (exclusion limit: 2 × 107, separation range: 100 to 2 × 107, theoretical plate count: 10,000 plates / column, packing material: styrene-divinylbenzene copolymer, packing particle size: 10 μm) in series. The number-average molecular weight can also be measured in a similar manner. The polydispersity can be calculated from the weight-average molecular weight and number-average molecular weight.
[0029] The glass transition temperature (Tg) of the acrylic resin (A) is preferably from -80 to 0°C, particularly preferably from -75 to -20°C, and further preferably from -70 to -35°C. If the glass transition temperature is too high, the adhesive strength tends to decrease, whereas if the glass transition temperature is too low, the acrylic resin tends to become too hard and the releasability tends to decrease.
[0030] The glass transition temperature is calculated by the following Fox formula. In this specification, the unit of Tg is "°C." Specifically, in the case of a polymer (homopolymer) consisting of only a single monomer, a standard analytical value described in, for example, "Polymer Data Handbook" compiled by the Society of Polymer Science can be adopted, and in the case of a copolymer obtained by polymerizing n types of monomers, the glass transition temperature can be considered to be calculated from the Tg of the homopolymer of each monomer.
[0031] 1 / Tg=w1 / Tg1+w2 / Tg2+·············Wk / Tgk where Tg is the glass transition temperature of the copolymer, and Tg1, Tg2, T gk is the Tg of the homocopolymer of each monomer component, and w1, w2,...wk represent the molar fraction of each monomer component, where w1 + w2 +...wk = 1.
[0032] [Biomass content of acrylic resin (A)] The proportion of plant-derived carbon in the acrylic resin (A), i.e., the biomass ratio, is 10% by weight or more, preferably 15% by weight, more preferably 20% by weight, and even more preferably 30% by weight or more, from the viewpoint of reducing the environmental load. The upper limit is 100% by weight. The biomass degree may be any value obtained by any of the calculation methods shown below, as long as it falls within the above range.
[0033] (How to calculate biomass ratio) Biomass content (wt%) of acrylic resin (A) = [(biomass content of each biologically-derived raw material used in producing acrylic resin (A)) × (total weight of each biologically-derived raw material used in producing acrylic resin (A)] / (total weight of acrylic resin (A)) × 100
[0034] The biomass ratio is also referred to as the biological carbon content, and can be determined by analyzing the composition ratio by NMR and calculating the carbon number of the biologically derived monomer / total carbon number.
[0035] While carbon derived from living organisms contains a certain percentage of the radioactive isotope (C-14), petroleum-derived carbon contains almost no C-14. Therefore, the biomass content can also be calculated by measuring the concentration of C-14 contained in the adhesive. Specifically, this can be measured in accordance with ASTM D6866, a standard used in many bioplastic industries.
[0036] <Crosslinking agent (B)> Next, the crosslinking agent (B) used in the present invention will be described. The crosslinking agent (B) contains a metal chelate-based crosslinking agent (b1), and may also contain a crosslinking agent that forms a chemical crosslink, such as an isocyanate-based crosslinking agent, an epoxy-based crosslinking agent, an aziridine-based crosslinking agent, a melamine-based crosslinking agent, an aldehyde-based crosslinking agent, or an amine-based crosslinking agent, or a crosslinking agent that forms a physical crosslink, such as a polyfunctional acrylate-based crosslinking agent.
[0037] Examples of the metal chelate crosslinking agent (b1) include acetylacetone and acetoacetyl ester coordination compounds of polyvalent metals such as aluminum, iron, copper, zinc, tin, titanium, nickel, antimony, magnesium, vanadium, chromium, and zirconium.
[0038] Examples of the isocyanate crosslinking agent include 2,4-tolylene diisocyanate, 2,6-tolylene diisocyanate, hydrogenated tolylene diisocyanate, 1,3-xylylene diisocyanate, 1,4-xylylene diisocyanate, hexamethylene diisocyanate, diphenylmethane-4,4-diisocyanate, isophorone diisocyanate, 1,3-bis(isocyanatomethyl)cyclohexane, tetramethylxylylene diisocyanate, 1,5-naphthalene diisocyanate, triphenylmethane triisocyanate, adducts of these polyisocyanate compounds with polyol compounds such as trimethylolpropane, and biuret and isocyanurate forms of these polyisocyanate compounds.
[0039] Examples of the epoxy crosslinking agent include bisphenol A-epichlorohydrin epoxy resins, ethylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, glycerin diglycidyl ether, glycerin triglycidyl ether, 1,6-hexanediol diglycidyl ether, trimethylolpropane triglycidyl ether, sorbitol polyglycidyl ether, polyglycerol polyglycidyl ether, pentaerythritol polyglycidyl erythritol, diglycerol polyglycidyl ether, 1,3'-bis(N,N-diglycidylaminomethyl)cyclohexane, and N,N,N',N'-tetraglycidyl-m-xylylenediamine.
[0040] Examples of the aziridine crosslinking agent include tetramethylolmethane-tri-β-aziridinylpropionate, trimethylolpropane-tri-β-aziridinylpropionate, N,N'-diphenylmethane-4,4'-bis(1-aziridinecarboxamide), and N,N'-hexamethylene-1,6-bis(1-aziridinecarboxamide). However, since such aziridine crosslinking agents have a short pot life and are mutagenic, their use may not be preferable depending on the intended use of the pressure-sensitive adhesive.
[0041] Examples of the melamine-based crosslinking agent include hexamethoxymethylmelamine, hexaethoxymethylmelamine, hexapropoxymethylmelamine, hexaptoxymethylmelamine, hexapentyloxymethylmelamine, hexahexyloxymethylmelamine, and melamine resins.
[0042] Examples of the aldehyde crosslinking agent include glyoxal, malondialdehyde, succindialdehyde, maleic dialdehyde, glutaric dialdehyde, formaldehyde, acetaldehyde, and benzaldehyde.
[0043] Examples of the amine-based crosslinking agent include hexamethylenediamine, triethyldiamine, polyethyleneimine, hexamethylenetetraamine, diethylenetriamine, triethyltetraamine, isophoronediamine, amino resins, and polyamides.
[0044] These crosslinking agents may be used alone or in combination of two or more kinds, but the metal chelate crosslinking agent (b1) is essential, and its content in the crosslinking agent (B) is preferably 50% by weight or more, 70% by weight or more, or 90% by weight or more.
[0045] The content of the crosslinking agent (B) is usually preferably 0.01 to 5 parts by weight, more preferably 0.05 to 1.5 parts by weight, and particularly preferably 0.1 to 1 part by weight, relative to 100 parts by weight of the acrylic resin (A). If the amount of crosslinking agent is too small, the cohesive strength tends to decrease and sufficient durability tends to be insufficient, while if the amount is too large, the flexibility and adhesive strength tend to decrease, making peeling more likely to occur.
[0046] The content of the metal chelate crosslinking agent (b1) is usually preferably 0.01 to 5 parts by weight, more preferably 0.05 to 1.5 parts by weight, and particularly preferably 0.1 to 1 part by weight, relative to 100 parts by weight of the acrylic resin (A). If the amount of crosslinking agent is too small, the cohesive strength tends to decrease and sufficient durability cannot be obtained, while if the amount is too large, flexibility and adhesive strength tend to decrease, making peeling more likely to occur.
[0047] Generally, when the content of the crosslinking agent in the pressure-sensitive adhesive composition is increased, the gel fraction of the pressure-sensitive adhesive layer increases, and therefore, the adhesive strength of the surface side of the pressure-sensitive adhesive layer is reduced. On the other hand, when the content of the crosslinking agent is reduced, the cohesive strength of the pressure-sensitive adhesive layer decreases, and as a result, the removability tends to decrease. For this reason, it has been difficult to satisfy all of the adhesive properties such as adhesive strength, removability, and tackiness in the past.
[0048] <Other additives> Furthermore, the pressure-sensitive adhesive composition of the present invention may contain various additives such as antistatic agents, other acrylic pressure-sensitive adhesives, other pressure-sensitive adhesives, tackifiers such as terpene resins, urethane resins, rosin, rosin esters, hydrogenated rosin esters, phenolic resins, aliphatic petroleum resins, alicyclic petroleum resins, and styrene resins, colorants, fillers, antioxidants, UV absorbers, and functional dyes, as well as compounds that change color or develop color upon exposure to UV or radiation, provided that the effects of the present invention are not impaired. In addition to the above additives, the pressure-sensitive adhesive composition may contain small amounts of impurities contained in the raw materials for producing the components of the pressure-sensitive adhesive composition. The amounts of these additives added may be appropriately determined so as to obtain the desired physical properties. Among these, it is preferable to add an antioxidant, since it can improve the stability of the resin over time.
[0049] <Adhesive tape> Next, a pressure-sensitive adhesive layer is formed using the pressure-sensitive adhesive composition of the present invention, thereby producing a pressure-sensitive adhesive tape. That is, the pressure-sensitive adhesive tape can be produced, for example, as follows. In the present invention, the term "adhesive tape" also includes those expressed as "adhesive sheet" and "adhesive film."
[0050] First, the pressure-sensitive adhesive composition is applied to one or both sides of a support substrate to a predetermined thickness, and then heated and dried to form a pressure-sensitive adhesive layer. Next, a release sheet is attached to the surface of the pressure-sensitive adhesive layer, if necessary, to produce a pressure-sensitive adhesive tape. The resulting pressure-sensitive adhesive tape is then subjected to an aging treatment, if necessary, and then, when in use, the release sheet is peeled off from the pressure-sensitive adhesive layer for use. In this way, a pressure-sensitive adhesive layer is formed on one or both sides of the support substrate, and a pressure-sensitive adhesive tape is obtained in which a release sheet is further provided on the surface of the pressure-sensitive adhesive layer, if necessary.
[0051] Examples of the support substrate include metal foils such as aluminum, copper, and iron; polyester resins such as polyethylene naphthate, polyethylene terephthalate, polybutylene terephthalate, and polyethylene terephthalate / isophthalate copolymer; polyolefin resins such as polyethylene, polypropylene, and polymethylpentene; polyethylene fluoride resins such as polyvinyl fluoride, polyvinylidene fluoride, and polyethylene fluoride; polyamides such as nylon 6 and nylon 6,6; vinyl polymers such as polyvinyl chloride, polyvinyl chloride / vinyl acetate copolymer, ethylene-vinyl acetate copolymer, ethylene-vinyl alcohol copolymer, polyvinyl alcohol, and vinylon; cellulose resins such as cellulose triacetate and cellophane; acrylic resins such as polymethyl methacrylate, polyethyl methacrylate, polyethyl acrylate, and polybutyl acrylate; synthetic resin films or sheets such as polystyrene, polycarbonate, polyarylate, and polyimide; paper such as fine paper and glassine paper; glass fiber; natural fiber; and synthetic fiber, and single-layer or multi-layer bodies selected from the following. The thickness of such a supporting substrate is usually 1 to 500 μm, and preferably 5 to 300 μm.
[0052] Furthermore, the release sheet may be, for example, any of the various synthetic resin sheets, paper, cloth, nonwoven fabric, etc. exemplified above as the supporting substrate, which have been subjected to a release treatment. Alternatively, a substrate-less adhesive tape can be produced by applying the above-mentioned adhesive composition to a release sheet, heating and drying the composition to form an adhesive layer, and then laminating a release sheet to the adhesive layer.
[0053] When applying the pressure-sensitive adhesive composition, it is preferable to dilute the pressure-sensitive adhesive composition in a solvent before application, and the dilution concentration is preferably 5 to 80% by weight, particularly preferably 10 to 70% by weight. The solvent may be any solvent that dissolves the pressure-sensitive adhesive composition, and examples of such solvents include ester-based solvents such as methyl acetate, ethyl acetate, methyl acetoacetate, and ethyl acetoacetate, ketone-based solvents such as acetone, methyl ethyl ketone, and methyl isobutyl ketone, aromatic solvents such as toluene and xylene, and alcohol-based solvents such as methanol, ethanol, and propyl alcohol. Among these, ethyl acetate, acetone, and toluene are preferably used in terms of solubility, drying properties, cost, etc.
[0054] The method for applying the pressure-sensitive adhesive composition is not particularly limited as long as it is a common coating method, and examples thereof include roll coating, die coating, gravure coating, comma coating, and screen printing.
[0055] The heating and drying conditions may be any conditions that allow the pressure-sensitive adhesive composition to be dried, such as a temperature of 50 to 150°C, preferably 60 to 130°C, for about 1 to 10 minutes, preferably 1.5 to 5 minutes.
[0056] The aging treatment is carried out to balance the adhesive properties, and the aging conditions are a temperature typically between room temperature (20°C±20°C) and 70°C, and a time typically between 1 and 30 days. Specifically, the aging treatment may be carried out under conditions such as 20°C for 1 to 20 days, or 40°C for 1 to 7 days.
[0057] Furthermore, the thickness of the adhesive layer in the obtained adhesive tape is usually preferably 10 to 100 μm, more preferably 15 to 60 μm, and particularly preferably 25 to 50 μm. If the thickness of this adhesive layer is too thin, the adhesive properties tend to be difficult to stabilize, while if it is too thick, drying becomes difficult and the amount of outgassing tends to increase.
[0058] The thickness of the adhesive tape thus obtained is set appropriately depending on the application, but is preferably set in the range of, for example, 20 to 300 μm.
[0059] When using the pressure-sensitive adhesive tape of the present invention, the type of adherend may be, for example, various articles having metal surfaces; polyester-based resins such as polyethylene naphthalate, polyethylene terephthalate, polybutylene terephthalate, and polyethylene terephthalate / isophthalate copolymer; polyolefin-based resins such as polyethylene, polypropylene, and polymethylpentene; Examples of the resin include polyethylene fluoride resins such as polyvinyl fluoride, polyvinylidene fluoride, and polyethylene fluoride; polyamides such as nylon 6 and nylon 6,6; vinyl polymers such as polyvinyl chloride, polyvinyl chloride / vinyl acetate copolymer, ethylene-vinyl acetate copolymer, ethylene-vinyl alcohol copolymer, polyvinyl alcohol, and vinylon; cellulose-based resins such as cellulose triacetate and cellophane; acrylic resins such as polymethyl methacrylate, polyethyl methacrylate, polyethyl acrylate, and polybutyl acrylate; and synthetic resin films, sheets, or plates such as polystyrene, polycarbonate, polyarylate, and polyimide.
[0060] Furthermore, examples of substrates to which the pressure-sensitive adhesive tape of the present invention can be applied as a protective tape include flooring and solid wood flooring (solid wood, plywood, two-layer, bamboo, paulownia, underfloor heating), laminate flooring (easy installation, DIY flooring, stone-grain, wood-grain), various tiles (ceramic, porcelain, natural stone, marble, ceramic, glass), mosaic tiles and glass flooring (natural stone, glass, ceramic, stainless steel, metal), cork flooring and sheet flooring (natural cork, non-slip flooring, linoleum, vinyl, CF, adhesive sheet flooring), paving materials and exterior flooring materials (stone, block, brick, tile, paving materials), painted flooring and underfloor materials (painted flooring, dustproofing, protective agents, cement-based self-leveling materials, floor insulation), interior carpeting, tatami mats (floor tatami mats, floor heating materials, hi-light tatami mats, tatami mats, edging mats, etc.), baseboards and aluminum baseboards (aluminum and resin profiles), and floor protective sheets with polyethylene laminated or embossed surfaces.
[0061] The gel fraction of the pressure-sensitive adhesive layer is usually 20 to 85%, preferably 30 to 80%, and particularly preferably 35 to 70%. If the gel fraction is too low, cohesive failure will occur during peeling, and adhesive residue will tend to be left behind, whereas if the gel fraction is too high, the adhesive strength will tend to decrease and the tackiness will tend to decrease.
[0062] The adhesive composition of the present invention is particularly suitable for use as an organic solvent-containing adhesive composition, and when cured by heat in the presence of a crosslinking agent to form an adhesive, it exhibits medium to high adhesive strength (approximately 3 N / 25 mm or more) and can be attached to an adherend for a short period of time (several weeks to several months) and then manually peeled off from the adherend. [Example]
[0063] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples as long as it does not depart from the gist of the invention. In the examples, "parts" and "%" are by weight.
[0064] First, various acrylic resins were prepared as follows: The weight average molecular weight, dispersity, glass transition temperature, and biomass ratio of the acrylic resins were measured according to the methods described above. The viscosity was measured in accordance with JIS K5400 (1990) 4.5.3 Rotational Viscosity Method. To measure the solid content, place 1 to 2 g of the resin solution on aluminum foil. It is calculated from the amount remaining after heating and drying for 60 minutes in an infrared dryer (185W, height 5cm). Solid content (%) = remaining amount after heat drying (g) / resin solution before heat drying (g) × 100
[0065] [Manufacturing Example 1] [Production of acrylic resin (A-1)] A 2L round-bottom, four-neck flask was charged with 250 g of ethyl acetate and stirred. The water bath temperature was set to 90°C. After refluxing began, a monomer mixture consisting of 255.0 g of 2-ethylhexyl acrylate, 200.0 g of 1-methylheptyl (meth)acrylate, 25.0 g of vinyl acetate, 19.5 g of acrylic acid, 0.5 g of 2-hydroxyethyl methacrylate, and 0.460 g of initiator AIBN was added dropwise over a two-hour period. Three hours after the start of the dropwise addition, 0.340 g of additional initiator AIBN and 50 g of dissolving solvent ethyl acetate were added. Five hours after the start of the dropwise addition, 0.300 g of additional initiator AIBN and 25 g of dissolving solvent ethyl acetate were added. Seven hours after the start of the dropwise addition, 0.150 g of additional initiator AIBN and 25 g of dissolving solvent ethyl acetate were added. Nine hours after the start of the reaction, 30 g of dilution solvent ethyl acetate and 120 g of isopropyl alcohol were added, and the mixture was then cooled to terminate the reaction, yielding acrylic resin (A-1) (weight-average molecular weight 540,000; dispersity 4.40; solids content 49.4%; viscosity 2500 mPa·s / 25°C). The reaction was carried out while maintaining the internal temperature at 78 to 87°C from the start to the end of the reaction.
[0066] [Manufacturing Example 2] [Production of acrylic resin (A-2)] A 2L round-bottom, four-neck flask was charged with 290 g of ethyl acetate and stirred. The water bath temperature was set to 90°C. After refluxing began, a monomer mixture consisting of 255.0 g of 1-methylheptyl (meth)acrylate, 200.0 g of butyl acrylate, 25.0 g of vinyl acetate, 19.5 g of acrylic acid, 0.5 g of 2-hydroxyethyl methacrylate, and 0.460 g of initiator AIBN was added dropwise over a two-hour period. Three hours after the start of the dropwise addition, 0.340 g of additional initiator AIBN and 50 g of dissolving solvent ethyl acetate were added. Five hours after the start of the dropwise addition, 0.300 g of additional initiator AIBN and 25 g of dissolving solvent ethyl acetate were added. Seven hours after the start of the dropwise addition, 0.150 g of additional initiator AIBN and 25 g of dissolving solvent ethyl acetate were added. Nine hours after the start of the reaction, 110 ml of isopropyl alcohol as a dilution solvent was added, and the mixture was then cooled to terminate the reaction, yielding acrylic resin (A-2) (weight-average molecular weight 680,000; dispersity 5.19; solids content 50.3%; viscosity 9,300 mPa·s / 25°C). The reaction was carried out while maintaining the internal temperature at 78 to 85°C from the start to the end of the reaction.
[0067] [Manufacturing Example 3] [Production of acrylic resin (A-3)] A 2L round-bottom, four-neck flask was charged with 250 g of ethyl acetate and stirred. The water bath temperature was set to 95°C. After refluxing began, a monomer mixture consisting of 150.0 g of 2-ethylhexyl acrylate, 300.0 g of 1-methylheptyl (meth)acrylate, 25.0 g of vinyl acetate, 19.5 g of acrylic acid, 0.5 g of 2-hydroxyethyl methacrylate, and 0.460 g of initiator AIBN was added dropwise over a two-hour period. Three hours after the start of the dropwise addition, 0.340 g of additional initiator AIBN and 50 g of dissolving solvent ethyl acetate were added. Five hours after the start of the dropwise addition, 0.300 g of additional initiator AIBN and 25 g of dissolving solvent ethyl acetate were added. Seven hours after the start of the dropwise addition, 0.150 g of additional initiator AIBN and 25 g of dissolving solvent ethyl acetate were added. Nine hours after the start of the reaction, 150 g of ethyl acetate as a dilution solvent was added, and the mixture was then cooled to terminate the reaction, yielding acrylic resin (A-3) (weight-average molecular weight 560,000; dispersity 5.01; solids content 49.5%; viscosity 2750 mPa·s / 25°C). The reaction was carried out while maintaining the internal temperature at 78 to 88°C from the start to the end of the reaction.
[0068] [Manufacturing Example 4] [Production of acrylic resin (A-4)] A 2L round-bottom, four-neck flask was charged with 250 g of ethyl acetate and stirred. The water bath temperature was set to 95°C. After refluxing began, a monomer mixture consisting of 55.0 g of 2-ethylhexyl acrylate, 400.0 g of 1-methylheptyl (meth)acrylate, 25.0 g of vinyl acetate, 19.5 g of acrylic acid, 0.5 g of 2-hydroxyethyl methacrylate, and 0.460 g of initiator AIBN was added dropwise over a two-hour period. Three hours after the start of the dropwise addition, 0.340 g of additional initiator AIBN and 50 g of dissolving solvent ethyl acetate were added. Five hours after the start of the dropwise addition, 0.300 g of additional initiator AIBN and 25 g of dissolving solvent ethyl acetate were added. Seven hours after the start of the dropwise addition, 0.150 g of additional initiator AIBN and 25 g of dissolving solvent ethyl acetate were added. Nine hours after the start of the reaction, 150 g of ethyl acetate as a dilution solvent was added, and the mixture was then cooled to terminate the reaction, yielding acrylic resin (A-4) (weight-average molecular weight 580,000; dispersity 4.63; solids content 49.4%; viscosity 3510 mPa·s / 25°C). The reaction was carried out while maintaining the internal temperature at 78 to 88°C from the start to the end of the reaction.
[0069] [Manufacturing Example 5] [Production of acrylic resin (A'-1)] A 2L round-bottom, four-neck flask was charged with 250 g of ethyl acetate and stirred. The water bath temperature was set to 90°C. After refluxing began, a monomer mixture consisting of 455.0 g of 1-methylheptyl (meth)acrylate, 25.0 g of vinyl acetate, 19.5 g of acrylic acid, 0.5 g of 2-hydroxyethyl methacrylate, and 0.460 g of initiator AIBN was added dropwise over two hours. Three hours after the start of the dropwise addition, 0.340 g of additional initiator AIBN and 50 g of dissolving solvent ethyl acetate were added. Five hours after the start of the dropwise addition, 0.300 g of additional initiator AIBN and 25 g of dissolving solvent ethyl acetate were added. Seven hours after the start of the dropwise addition, 0.150 g of additional initiator AIBN and 25 g of dissolving solvent ethyl acetate were added. Nine hours after the start of the reaction, 30 g of dilution solvent ethyl acetate and 120 g of isopropyl alcohol were added, and the mixture was then cooled to terminate the reaction, yielding acrylic resin (A'-1) (weight-average molecular weight 630,000; dispersity 5.36; solids content 49.8%; viscosity 4160 mPa·s / 25°C). The reaction was carried out while maintaining the internal temperature at 78 to 85°C from the start to the end of the reaction.
[0070] [Table 1]
[0071] The following crosslinking agent (B) was prepared: (b1-1): Aluminum acetylacetonate (manufactured by Mitsubishi Chemical Corporation; trade name "Coponyl 5792") (b'-1): Trimethylolpropane / tolylene diisocyanate adduct (manufactured by Mitsui Chemicals, Inc.; product name "Takenate D101E")
[0072] Example 1 100 parts (solid content equivalent) of the acrylic resin (A-1) was mixed with 0.45 parts of crosslinking agent (b-1), and the mixture was diluted with ethyl acetate to a viscosity suitable for coating to obtain a pressure-sensitive adhesive composition.
[0073] <Examples 2, 3, and 4, Comparative Examples 1 and 2> A pressure-sensitive adhesive composition was obtained in the same manner as in Example 1, except that the blending amounts of each component were as shown in Table 2.
[0074] [Table 2]
[0075] [Preparation of adhesive tape] The pressure-sensitive adhesive compositions produced in Examples 1 to 4 and Comparative Examples 1 and 2 were applied to a release PET (polyethylene terephthalate film) (Mitsui Chemicals Tocello, Inc., trade name "SP-PET38-01") using an applicator so that the film thickness after drying would be 40 μm, and then dried at 80° C. for 4 minutes. Thereafter, the formed pressure-sensitive adhesive layer side was laminated to untreated PET (38 μm film thickness; Toray Industries, Inc., trade name "Lumirror 38T60"), followed by aging at 40° C. for 3 days to obtain a pressure-sensitive adhesive tape.
[0076] <Adhesive strength> The adhesive tape obtained above was cut to a width of 25 mm and a length of 100 mm. The release PET film was peeled off, and the adhesive layer side was attached to the substrate ((1) SUS304BA plate; (2) SUS304 polished according to JIS Z-0237 "Test Method for Adhesive Tapes and Sheets") by pressing with a 2 kg rubber roller twice in a 50% relative humidity atmosphere at 23°C. After leaving the tape in the same atmosphere for 30 minutes, the 180° peel strength (N / 25 mm) was measured using a Shimadzu Autograph AG-X tensile tester at a peel rate of 300 mm / min, and the peeling condition was observed. The results are shown in Table 3. Peeling state Interfacial peeling: Peeling was achieved at the adherend interface without contaminating the adherend. Cohesive failure: Cohesive failure occurred and adhesive residue was observed on the adherend.
[0077] <Holding force> The PET film with adhesive layer for each example was cut to a size of 25 mm x 50 mm, and the release sheet was peeled off. A stainless steel plate (SUS304) was placed on the exposed adhesive layer side, and a 2 kg roller was applied back and forth to apply pressure to the film (adhesion area 25 mm x 25 mm). A creep tester (Tester Sangyo Co., Ltd., BE-501, constant humidity chamber equipped holding force tester) was used to apply a 1 kg load and measure the distance of displacement in an 80°C atmosphere for 24 hours. The results are shown in Table 3.
[0078] <Tuck> In accordance with JIS Z-0237 "Test Methods for Adhesive Tapes and Sheets," the ball tack of the resulting adhesive tape was measured with an inclined plate angle of 30° and a runway length of 100 mm. The evaluation criteria are as follows. The results are shown in Table 3. (Evaluation criteria) ○…No.7 or above △…No.5~No.6 ×…No.2~N.4
[0079] <Removability> The resulting PET film with adhesive layer was used to prepare (cut out) a test piece measuring 25 mm wide x 50 mm long. This test piece was then pressed against an adherend ((1) unpolished SUS) using a 2 kg roller, which was then rolled back and forth twice. The test piece was then left in a 40°C atmosphere for 3 days and then returned to 23°C. Approximately 3 / 5 of the total length was peeled off by hand at a peeling speed of 300 mm / min in a 45° direction, and the remaining portion was then peeled off at a higher speed. The condition of the adherend surface after peeling was observed and evaluated according to the following criteria. The results are shown in Table 3. (Evaluation criteria) ○: No adhesive residue or slight adhesive residue visible on the edge △: Small amounts of glue residue were scattered or glue residue was found in less than 50% of the total surface area ×: Adhesive residue was found on 50% or more of the total surface area, or the adhesive peeled off from the substrate and stuck to the adherend.
[0080] [Table 3]
[0081] Examples 1 to 4, which used the pressure-sensitive adhesive composition of the present invention, exhibited excellent adhesive properties, such as adhesion, holding power, and tackiness, to various adherends, while also exhibiting good releasability. On the other hand, Comparative Examples 1 and 2, which did not use the pressure-sensitive adhesive composition of the present invention, exhibited poor tackiness. [Industrial Applicability]
[0082] The pressure-sensitive adhesive composition of the present invention and a pressure-sensitive adhesive prepared using the same are pressure-sensitive adhesive compositions for obtaining pressure-sensitive adhesives that have a good balance of adhesive properties (adhesion, holding power, tack) and releasability for a variety of adherends, and are useful as protective tapes that do not leave adhesive residue when removed.
Claims
1. A pressure-sensitive adhesive composition containing an acrylic resin (A) and a crosslinking agent (B), With respect to all structural units of the acrylic resin (A), the content of structural units derived from 1-methylheptyl (meth)acrylate (a1) is 10 to 90% by weight, and the content of structural units derived from the ethylenically unsaturated monomer containing a functional group (a2) is 0.1 to 10% by weight, The pressure-sensitive adhesive composition, wherein the crosslinking agent (B) contains a metal chelate crosslinking agent (b1).
2. 2. The pressure-sensitive adhesive composition according to claim 1, wherein the acrylic resin (A) has a glass transition temperature (Tg) of −30° C. or lower.
3. 2. The pressure-sensitive adhesive composition according to claim 1, wherein the content of the crosslinking agent (B) is 0.01 to 5 parts by weight based on 100 parts by weight of the acrylic resin (A).
4. The pressure-sensitive adhesive composition according to claim 1, wherein the proportion of plant-derived carbon in the entire pressure-sensitive adhesive composition is 10% by weight or more.
5. A pressure-sensitive adhesive obtained by crosslinking the pressure-sensitive adhesive composition according to any one of claims 1 to 4.
6. An adhesive tape comprising an adhesive layer made of the adhesive according to claim 5.
Citation Information
Patent Citations
2-Octyl (meth)acrylate adhesive composition
JP2010506979A
2-Octyl (meth)acrylate adhesive composition
JP2011516690A
Adhesive composition, adhesive formed by hardening the same and adhesive tape
JP2015189842A